2020
DOI: 10.1007/s00345-020-03318-5
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted mini-percutaneous nephrolithotomy: a new perspective in fragments clearance and intrarenal pressure control

Abstract: Purpose To describe the vacuum-assisted mini-percutaneous nephrolithotomy (vmPCNL) technique performed via the 16Ch ClearPetra sheath, to evaluate its outcomes and to analyze intrarenal pressure (IRP) fluctuations during surgery. Methods Data from all consecutive vmPCNL procedures from September 2017 to October 2019 were prospectively collected. Data included patients' and stones characteristics, intra and peri-operative items, post-operative complications and stone clearance. Patients undergoing vmPCNL from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
(23 reference statements)
1
28
0
1
Order By: Relevance
“…Moreover, shorter OT may help limiting infectious complication by reducing the time span during which surgery is performed at elevated intra-pelvic pressure. Aspiration-assisted mPCNL techniques have already been proved to be associated with less bleeding [ 10 , 23 ], lower renal pelvic pressures and subsequent infectious complications [ 6 , 12 , 14 , 24 ] than non-suctioning miniPCNL procedures. In this series we confirmed that infectious complications were lower for vmPCNL than MIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, shorter OT may help limiting infectious complication by reducing the time span during which surgery is performed at elevated intra-pelvic pressure. Aspiration-assisted mPCNL techniques have already been proved to be associated with less bleeding [ 10 , 23 ], lower renal pelvic pressures and subsequent infectious complications [ 6 , 12 , 14 , 24 ] than non-suctioning miniPCNL procedures. In this series we confirmed that infectious complications were lower for vmPCNL than MIP.…”
Section: Discussionmentioning
confidence: 99%
“…However, several Authors have proposed the use of various PCNL sheaths or nephroscopes equipped with suctioning mechanisms with promising outcomes [8][9][10][11]. Among the new instruments, the vacuum-assisted mini PCNL (vmPCNL) is a safe and effective treatment option for kidney stones [12,13]. Previous Authors have shown that vmPCNL was associated with shorter OT, reduced use of accessory devices for stone removal and lower intra-pelvic pressures than mini-PCNL, thanks to its continuous aspiration system that allows for simultaneous lithotripsy and litholapaxy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, smaller instruments carry some limitations too, such as a reduced choice of lithotripsy and lapaxy probes, difficulties in fragment retrieval, longer operation time, reduced visual field, and higher intra renal pressure (IRP) [ 16 ]. In order to overcome these limitations, aspiration-integrated mini-PCNL systems have been developed in recent years, such as the Super Mini PCNL (SMP) and the vacuum-assisted mini-PCNL performed by means of the Clear Petra system [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, mini-PCNL presents several shortcomings such as difficult stone fragment extraction, extended operative time, and elevated renal pelvic pressure [1, [10][11][12]. Previous studies have reported that the vacuum-assisted sheath DOI: 10.1159/000518259 (ClearPetra; Well Lead Medical) in mini-PCNL allows the surgeon to obtain very good control over renal pelvic pressure [13][14][15]. Nevertheless, the inflow and outflow occur in the same cavity of this vacuum-assisted sheath.…”
Section: Introductionmentioning
confidence: 99%